Investigation of the Dynamic Characterization of Traditional and Modern Building Materials Using an Impact Excitation Test - Anil Ozdemir (Buildings)
This study presents a comprehensive non-destructive evaluation of a broad range of construction materials using the impulse excitation of vibration (IEV) technique. Tested specimens included low- and normal-strength concrete, fiber-reinforced concrete (with basalt, polypropylene, and glass fibers), lime mortars (NHL-2 and -3.5), plaster, and clay bricks (light and dark). Compressive and flexural strength tests complemented dynamic resonance testing on the same samples to ensure full mechanical characterization. Flexural and torsional resonance frequencies were used to calculate dynamic elastic modulus, shear modulus, and Poisson’s ratio. Strong correlations were observed between dynamic elastic modulus and shear modulus, supporting the compatibility of dynamic results with the classical elasticity theory. Flexural frequencies were more sensitive to material differences than torsional ones. Fiber additives, particularly basalt and polypropylene, significantly improved dynamic stiffness, increasing the dynamic elastic modulus/compressive strength ratio by up to 23%. In contrast, normal-strength concrete exhibited limited stiffness improvement despite higher strength. These findings highlight the reliability of IEV in mechanical properties across diverse material types and provide comparative reference data for concrete and masonry applications.